Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di SMP Negeri Matap - Andi S. Lapaimalai; Nehemia Fanpada (Peneliti.net, 2022)
Teacher performance cannot develop without the support of various parties or the efforts of the principal. Support from family and support from the community is needed by a teacher to improve his performance at school. The principal plays an important role in managing an educational institution so that the process of developing teacher performance can increase to become a professional teacher in the field of science. Based on observations made by researchers that at Matap State Junior High School located in Wolwal Barat Village, Alor Barat Daya Subdistrict, Alor Regency, there are 13 educators consisting of 2 CPNS and 11 Non Civil Servants who have different abilities or talents. in various fields of study and has 4 teaching staff. Researchers found several problems in the principal's management of teacher performance, namely the principal has not motivated teachers well, the principal has not disciplined and supervised the teachers properly, most teachers are late for school, teachers and principals are less involved in realizing the vision and mission or goals of the school so that it greatly affects the performance of teachers in schools and there are teachers who have not prepared learning tools properly when applying learning materials in class. The limitation of the problem in this research is the Influence of Principal Leadership on Teacher Performance at SMP Negeri Matap. The formulation of the problem is whether there is an influence of Principal Leadership on Teacher Performance at SMP Negeri Matap. The purpose of the study was to determine the effect of principal's leadership on teacher performance at SMP Negeri Matap. The population and sample are all 13 teachers. The data analysis technique used instrument test, validity test and instrument reliability test. The result of the research is that there is a significant influence of principal's leadership on teacher performance at SMP Negeri Matap, namely Fcount = 9.981 Ftable = 4.96 at a significant level of 0.05 or 5%. Then reject H0, accepted Ha.